METHODOLOGY OF FORMING THE SYSTEM OF ENSURING FINANCIAL STABILITY OF CREDIT INSTITUTIONS - O. I. Baranovskyi; M. E. Khutorna (Фінансово-кредитна діяльність: проблеми теорії та практики, 2018)
This paper is devoted to the research of methodological foundations for ensuring financial stability system of credit institutions. The ensuring credit institutions’ financial stability should be based on the value-oriented, risk-oriented approaches and, above all, on the systemic approach. The formation of a system of ensuring financial stability of credit institutions can’t be set only by the organizational and managerial influence on the unbalancing resources of the credit institutions, but also foresee an arrangement of an appropriate informal institutional environment that would serve as a world-view platform for successful implementation of measures on financial stability. Original results. It’s determined the nature of the system of ensuring financial stability of credit institutions, the goals and targets of its functioning, object and subject composition, internal structure and scientific principles that determine its nature and peculiarities of its interaction with the external environment. The main components of the studied system include: informal institutional environment; formal institutional environment; the methodical (cognitive) and supplying subsystems. The informal institutional environment is one. Its quality influence on the effectiveness of measures to ensure the financial stability of credit institutions and the ability to maintain it in a long-term period. Practical relevance. The functionality of the proposed system largely depends on the quality of corporate ethics and the depth of its implementation in the activities of credit institutions. Thus, fraudulent actions, provoked by a business entity (a credit institution), including intentional actions to create a crisis situation in the institution, cannot be turned away by the system. The proposed system is only capable of managing the real threats to financial stability, namely those caused by objective internal or external factors.